Profiling of kidney disease patients undergoing hemodialysis - Kalra, Vikram; Agarwal, Deepak; Anis, Yasir (International Journal of Research in Medical Sciences, 2025)
Background: Kidney failure represents a substantial global health challenge; however, hemodialysis functions as a vital treatment for end-stage renal disease (ESRD). This study offers insights into the causes (and) demographic distribution of kidney failure among patients undergoing hemodialysis in Haryana and Uttar Pradesh, India. Although there are various factors contributing to this condition, understanding the nuances is essential because it can help to formulate better healthcare strategies. Methods: A cross-sectional study (conducted by DCDC kidney care) involved 3,254 patients undergoing hemodialysis across Haryana and Uttar Pradesh. Data collected on demographic parameters, clinical characteristics and as per the clinical history of kidney failure were analyzed. Descriptive statistics helped to analyse age, gender and perceived causes of kidney failure; however, regional variations were highlighted. This study is significant, because it provides insights into the complexities of kidney failure, although it does have its limitations. Results: The majority of patients undergoing hemodialysis were middle-aged, with the highest representation in the 41-50 years (25.1%) and 31-40 years (22.1%) age groups. Male patients constituted 70.9% of the population. Hypertension was identified as the most prevalent cause of kidney failure (60.35%), followed by diabetes (17.02%) and painkiller misuse (21.30%). Self-reported causes varied regionally; blood pressure was the leading cause in both Haryana (68.3%) and Uttar Pradesh (45.6%). However, excessive drug use (13.7%) and other unspecified causes (15.6%) were more prominent in Uttar Pradesh. These findings underscore regional disparities in awareness, risk factors and healthcare practices. Conclusions: The study highlights the multifactorial nature of kidney failure, with hypertension, diabetes, and medication misuse being the primary contributors. Regional variations in the perceived causes of kidney failure reflect differences in risk factor awareness and healthcare practices between Haryana and Uttar Pradesh. Tailored interventions addressing modifiable risk factors and regional disparities are crucial for effective prevention and management of kidney failure.